2018
DOI: 10.1063/1.5018303
|View full text |Cite
|
Sign up to set email alerts
|

Forward-flux sampling with jumpy order parameters

Abstract: Forward-flux sampling (FFS) is a path sampling technique that has gained increased popularity in recent years and has been used to compute rates of rare event phenomena such as crystallization, condensation, hydrophobic evaporation, DNA hybridization, and protein folding. The popularity of FFS is not only due to its ease of implementation but also because it is not very sensitive to the particular choice of an order parameter. The order parameter utilized in conventional FFS, however, still needs to satisfy a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 67 publications
10
81
0
Order By: Relevance
“…Since brute force results contain no approximation, and they can be regarded as a benchmark for methodologies aiming to estimate J for nucleation, these results support the validity of CNT in describing the nucleation behaviour of colloidal electrolytes (at least at T* = 1). The discrepancy between the Seeding and FFS nucleation rates is somewhat not surprising since, on the one hand, it has been previously found that FFS calculations may underestimate the nucleation rate by a few orders of magnitude when the sampling is not extremely large, 26,44,114,115 and on the other, because Seeding results may also have an uncertainty (systematic + statistical) of about 3-5 orders of magnitude in the nucleation rate (see Fig. 5).…”
Section: B Crystal Nucleation Rate Of the Different Polymorphsmentioning
confidence: 85%
“…Since brute force results contain no approximation, and they can be regarded as a benchmark for methodologies aiming to estimate J for nucleation, these results support the validity of CNT in describing the nucleation behaviour of colloidal electrolytes (at least at T* = 1). The discrepancy between the Seeding and FFS nucleation rates is somewhat not surprising since, on the one hand, it has been previously found that FFS calculations may underestimate the nucleation rate by a few orders of magnitude when the sampling is not extremely large, 26,44,114,115 and on the other, because Seeding results may also have an uncertainty (systematic + statistical) of about 3-5 orders of magnitude in the nucleation rate (see Fig. 5).…”
Section: B Crystal Nucleation Rate Of the Different Polymorphsmentioning
confidence: 85%
“…5, and we will discuss it below. Besides, there is a recent paper 30 which reveals that although FFS is not sensitive to order parameter, the conventional FFS sometimes still underestimates the nucleation rate by several orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the low saving frequency might lead to large jumps in the order parameter from one frame to the next. The effect of such jumpiness has been studied in the context of FFS in ref ( 64 ).…”
Section: Methodsmentioning
confidence: 99%